Risk factors for right paraesophageal lymph node metastasis in papillary thyroid carcinoma: A meta-analysis. (March 2020) - Shao, Liang; Sun, Wei; Zhang, Hao; Zhang, Ping; Wang, Zhihong; Dong, Wenwu; He, Liang; Zhang, Ting; Qin, Yuan
Abstract: Objective: Prophylactic dissection of the right paraesophageal lymph node (RPELN) in thyroid cancer is controversial. We performed a meta-analysis to provide evidence for RPELN dissection in thyroid cancer. Methods: We searched the PubMed and Science Citation Index Expanded (SCIE) databases for relevant studies published up to January 31, 2019. The patients involved all had a pathological diagnosis of papillary thyroid cancer (PTC) and had undergone total thyroidectomy or right lobectomy with central compartment lymph node dissection. The RPELNs had been kept aside during the operation. Results: Fourteen cohort studies involving 11, 090 patients with PTC were included in the meta-analysis. There was RPELN metastases (RPELNM) in 1038 patients (9.36%). The factors related to RPELNM were: age <45 years, male sex, right lobe tumor, tumor >1 cm, extrathyroidal extension, capsular invasion, right paratracheal lymph node metastasis (RPTLNM), central lymph node metastasis (CLNM), lateral lymph node metastasis (LLNM), and tumor multifocality. There was no association between RPELNM and Hashimoto's thyroiditis (HT) and inferior pole tumors or tumor in the middle of the gland. With superior pole tumors, there was even less RPELNM. Conclusions: The clinical features related to RPELNM are age <45 years, male sex, tumor >1 cm, tumor diameter >2 cm, right lobe tumor, RPTLNM, extrathyroidal extension, capsular invasion, CLNM, CLNM ≥3, LLNM and multifocality, which should be considered when evaluating RPELN dissection. Highlights: Includes 14 articles involving 11, 090 patients to analysis risk factor for RPELNM. Confirmed age, male sex, tumor diameter, position, RPTLNM, ETE, capsular invasion, CLNM, LLNM and multifocality as risk factor for RPELNM. Provides more powerful evidence for surgeons to develop surgical strategies.